Prevalence of Nocturnal Enuresis and Its Associated Factors in Primary School and Preschool Children of Khorramabad in 2013 - Katayoun Bakhtiar; Yadollah Pournia; Farzad Ebrahimzadeh; Ali Farhadi; Fathollah Shafizadeh; Reza Hosseinabadi (Hindawi Limited, 2014)
Background. Nocturnal enuresis refers to an inability to control urination during sleep. This study aimed to determine the prevalence of nocturnal enuresis and its associated factors in children in the city of Khorramabad. Materials and Methods. In this descriptive-analytic, cross-sectional study, 710 male and female children were divided into two groups with equal numbers. The samples were selected from the schools of Khorramabad using the multistage cluster and stratified random sampling methods based on the diagnostic criteria of DSM-IV. The data was analyzed using the logistic regression. Results. The results showed that 8% of the children had nocturnal enuresis, including 5.2% of primary nocturnal enuresis and 2.8% of secondary nocturnal enuresis. The prevalence of nocturnal enuresis in the boys (10.7%) was higher compared with that in the girls (5.4%) (P=0.009). There were statistically significant relationships between nocturnal enuresis and history of nocturnal enuresis in siblings (P=0.023), respiratory infections (P=0.036), deep sleep (P=0.007), corporal punishment at school (P=0.036), anal itching (P=0.043), and history of seizures (P=0.043). Conclusion. This study showed that the prevalence of nocturnal enuresis in the boys was higher compared with that in the girls.